Imipramine-induced mania in a child diagnosed with attention-deficit/hyperactivity disorder (ADHD): a case report - Yektas, Cigdem; Tufan, Ali Evren (TAYLOR \& FRANCIS LTD, 2018)
Children and adolescents treated with antidepressants (ADs) are at higher risk for developing hypomania and mania compared with adults. It was suggested that AD-induced mania represent a predisposition to bipolar disorder (BD) so it may accelerate the course of BD in this risky population. According to the literature, susceptibility to manic conversion with the use of ADs is higher in BD patients treated with tricyclic ADs compared with selective serotonin reuptake inhibitors (SSRIs) and placebo. Here, we report a six-year-old girl who was diagnosed with attention-deficit/hyperactivity disorder (ADHD) and primary nocturnal enuresis who developed manic symptoms after imipramine treatment. While using tricyclic antidepressants or SSRIs for different indications in the paediatric population, clinicians should be alert for the manic switch or behavioural activation symptoms, which may show a bipolar predisposition.
Keywords: Imipramine; mania; behavioural activation; ADHD; children and adolescents; bipolar disorder